Tapioca-resistant maltodextrin enhances probiotic survival more effectively than commercial prebiotics under simulated gastrointestinal conditions - Namkieat Pichamon; Borompichaichartkul Chaleeda; Dwi Ayuni; Suwimol Sapwarobol; Putthapong Phumsombat (Food Bioscience, 2025)
This study evaluated the protective efficacy of tapioca-resistant maltodextrin (TRM) on the gastrointestinal survivability of six probiotic strains— Lactobacillus acidophilus DDS-1®, L. rhamnosus LGG®, L. salivarius B37, L. paracasei 431®, Bifidobacterium breve M16V, and B. longum UABI-14—under simulated oral, gastric, and intestinal conditions. TRM, tested at 25%, 50%, and 100% (w/w), was compared to inulin, fructooligosaccharides (FOS), and konjac glucomannan hydrolysate (KGMH). In the absence of prebiotics, probiotic viability declined markedly post-gastric digestion ( p < 0.001). TRM significantly improved survivability, particularly at 100%, where L. acidophilus DDS-1 and L. rhamnosus LGG® retained >6 log CFU/mL. B. breve UABI-14 exhibited a gain exceeding 3.5 log CFU/mL, indicating strain-specific benefits. TRM also lowered terminal intestinal pH ( p < 0.001), suggesting enhanced fermentative activity. These findings highlight TRM as a promising prebiotic candidate for synbiotic applications, offering robust protection during gastrointestinal transit and supporting a favorable gut environment for probiotic function.
Keywords: Probiotics and Fermented Foods; Food composition and properties; Microbial Metabolites in Food Biotechnology